POTENTIAL ENTOMOPATHOGENIC BACTERIA ISOLATED FROM EXTREME CONDITION AREA SIDOARJO MUD, INDONESIA AGAINST Spodoptera litura FAB (LEPIDOPTERA: NOCTUIDAE) - Tita Widjayanti; Luqman Qurata Aini; Restu Rizkyta Kusuma; Istiqomah Istiqomah (BUANA SAINS, 2023)
Biological control by using entomopathogenic bacteria shows potential to be developed as an alternative technique to control Spodoptera litura. Bacteria that can live in extreme environments are reported to have high efficiency and the ability to survive in various environmental conditions, such as in the area of Sidoarjo mud. Related to the issue, this research aimed to find out bacteria that can survive in extreme conditions and are potentially entomopathogenic to control S. litura. The study was conducted from January until July 2021 in the Sidoarjo mud area and laboratory of Biological Control, Faculty of Agriculture, University of Brawijaya. The research was conducted using methods including consist of a sampling of Sidoarjo hot mud, isolation, and screening of bacteria that is potential as entomopathogenic bacteria, bioassay of mortality S. litura, development of larvae and pupal using Completely Randomized Design with 11 treatments and 4 replications, and molecular identification by 16S rRNA. Data for mortality and development of larvae and pupal were submitted to variance analysis, followed in comparison to the averages of the Duncan test at a 5% level of significance. The results showed that 43 colony bacteria from Sidoarjo hot mud have been successfully isolated and obtained 9 isolates selected as entomopathogenic bacteria against S. litura with a percentage of mortality larvae reached 60%. Moreover, bacteria have the potential to inhibit the development of larvae and pupal S. litura. Molecular identification showed that potential isolates are Bacillus subtilis strain 15A-B92, Bacillus thuringiensis strain GTG-29, and Bacillus anthracis strain BA1035.